Nano-vascularized polymers: how nanochannels impact the mechanical behaviour at the macroscale. (October 2022) - Cocchi, D.; Pirondi, A.; Brugo, T.M.; Boi, M.; Graziani, G.; Baldini, N.; Zucchelli, A.
Abstract: In recent decades, nature has inspired the engineering of many structural and smart materials. Nano-vascularization has been stimulating research on advanced materials for novel biomedical, orthopaedic, industrial, and aeronautical applications. The continuous development of nano-vascularized materials requires a more accurate understanding of their mechanical behaviour. This work provides a multiscale methodology to predict the macroscale properties of nano-vascularized materials. The methodology is experimentally validated for the case of a nano-vascularized epoxy resin manufactured using sacrificial electrospun nanofibers. It is based on the development of representative volume elements (RVEs) that encompass information about both the nanochannels distribution and on the mechanical properties of the material at different dimensional scales. The RVEs simulations allowed obtaining a homogenized model describing the nano-vascularized material properties and studying the most intimate failure mechanisms. A virtual stress tomographic investigation on the RVEs was adopted as a digital twin to reveal the damage evolution and the actual failure mechanisms of the nano-vascularized material: damage occurred mainly at the nanochannels intersections, particularly where the intersections become dense. Interestingly, the simulations revealed a correlation between the stress state and the formation of feather markings as well as local failures on the nanochannels linking directions, as evidenced by SEM analysis. Graphical abstract: ga1 Highlights: New Digital Twin methodology predicts the behaviour of nano-vascularized materials Innovative virtual stress tomography to study failure mechanisms at the nanoscale Numerical stress-strain results within 3% respect to experimental ones The higher nanochannels density the higher stress intensity FEA describes damage and stress relaxation at nanoscale as observed in SEM images